Lateral flow assay as radiological prognosis factor of pulmonary cryptococcosis: a single center retrospective study in China - Shi, Jiejun; Chen, Jianhua; Ding, Qianjiang; Qian, Guoqing; Zhang, Zeqin; Song, Qifa (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundLateral flow assay (LFA) has demonstrated high sensitivity and specificity for diagnosing cryptococcosis. However, its role in predicting therapeutic efficacy for pulmonary cryptococcosis (PC) remains underexplored.MethodsWe conducted a retrospective analysis of HIV-negative patients with PC to describe the clinical profile and identify potential predictors of radiological prognosis.ResultsAll the 168 participants received antifungal therapy with a triazole agent. Of these, 84.5% experienced partial or complete absorption of pulmonary lesions. The results of the gamma test, chi-square trend test, and ordinal logistic regression all indicated that both baseline LFA and changes in LFA after treatment were significant predictors of imaging prognosis. The degree of radiological improvement was inversely associated with the baseline LFA positive grade(P for linear-by-linear association: 0.011, Spearman correlation coefficient = -0.17; γ= -0.368, P = 0.045). Patients with a decrease in LFA after therapy had significantly better radiological outcomes compared to those with equal or increased LFA(linear-by-linear association, P = 0.014, Spearman correlation coefficient = 0.188; γ = 0.371, P = 0.012). Additionally, favorable outcomes were more likely in patients with lesions confined to the right lung.ConclusionsLFA shows potential of monitoring radiological outcomes in pulmonary cryptococcosis.